Aspas verbo-visuais - Vianna, Rodolfo (2016)
This thesis is intended to present the concept of verbal-visual quotation marks and categories of analysis for the study of the phenomenon covered. The pursued hypothesis is that, “by taking into account the utterance in its verbal-visual dimension, certain relations between its constitutive verbal and visual elements may constitute opacifying meta-enunciative unfoldings –in analogy with the dynamics of autonymic modalization present in the verbal dimension– and be considered as verbal-visual quotation marks.” The hypothesis suggests the possibility of expanding the meaning of a given visual element when comprehending the constitutive verbal-visual dimension of the utterance, likewise when quotation marks are employed in the strictly verbal dimension, i.e., constituting itself as a sort of presence/absence to be filled out by interpretation. The research aims to answer three questions. 1) How to understand the process of meta-enunciation, which is constitutive of the autonymic modalization, in the verbal-visual dimension? 2) What would be and how are constructed the opacifying meta-enunciative unfoldings (autonymic modalization) between verbal and visual elements based on the verbal-visual dimension of the enunciated utterances listed in the corpus of this research? 3) Which similarities amongst the occurrences of verbal-visual quotation marks allow developing categories of analysis for the phenomenon at issue? The corpus of analysis consists on news selected from the daily papers Folha de S.Paulo and O Estado de S.Paulo and the weekly magazine Veja in the period from September 23, 2012, to October 20, 2012. In answering the aforementioned questions under the postulated hypotheses, this thesis articulates the formulations of Authier-Revuz on autonymic modalization, the notions of concrete utterance and ideological sign stemmed from Bakhtin Circle, the studies on verbal visuality developed by Brait and the concept of instance of complex enunciation formulated by Maingueneau. Besides confirming the hypothesis by means of the analysis conducted in this study, the research presents three categories of verbal-visual quotation marks, namely direct relation between verbal and visual elements, opacification of the verbal elements in the visual dimension, and opacifying verbal-visual allegory. The intended contribution to both Applied Linguistics and Language Studies in general is to circumscribe the comprehension of the enunciative-discursive phenomenon that produces meaning by articulating the verbal and visual dimensions of the utterance, postulating the concept of verbal-visual quotation marks, and to offer categories of analysis that can be shared by future research on the effects of meanings produced in the articulation between images and verbal texts